Exploring the Life of College Students with Attention Deficit Hyperactivity Disorder - Halim, Nurul Husna Binti Abdul; Arifin, Zainal; Daulay, Annisa Arumaisyah (International Journal of Multidisciplinary Research of Higher Education, 2025)
This study aims to analyze the experiences of adult Attention Deficit Hyperactivity Disorder (ADHD) sufferers among students in Higher Education Malaysia in living their daily lives. The method used is qualitative with a descriptive approach. The research subjects consisted of two people, namely students of the Malaysian Institute of Higher Education. This research was conducted with data collection techniques through interviews, observations, and literature studies. Data analysis was carried out with the stages of data reduction, data presentation, and conclusion drawing. The results showed that Attention Deficit Hyperactivity Disorder (ADHD) in adults, especially university students, causes symptoms such as hyperactivity, anxiety, and cognitive confusion that interfere with academic and social activities. However, sufferers can manage these symptoms through self-adjustment, professional therapy and spiritual approaches, which contribute to improved emotional stability and productivity in daily life. This study confirms the importance of holistic support to help adults with Attention Deficit Hyperactivity Disorder (ADHD) lead more organized and meaningful lives.